THE EFFECT OF ADOPTION OF IFRS BASED ACCOUNTING STANDARDS: INDIAN EVIDENCES OF ENHANCED VALUE RELEVANCE AND UNIFORMITY - Banerjee, Somnath; Dhar, Satyajit; Dutta, Anirban (International Journal of Accounting & Finance Review, 2021)
This study examines how relevant the accounting information was for the value of the firm prior to 2016, when India had the indigenous Accounting Standards, and after 2016 when India adopted new accounting standards known as IND-AS, which were the convergence standards mostly in line with IFRS. As an extension to this, we have performed another round of analysis to observe whether the enhanced value relevance is symmetrically distributed among big and small firms. We have used the price regression model of (Barth et al, 2008) on 1770 firm-years data of Indian firms and applied panel data analysis. We have found 66% adjusted R2 under OLS method for the period prior to 2016 and 78% for the post-change period. Further to this, big and small firms, in the new regime, have shown 84% and 89% adjusted R2. From the results, we have found substantial improvement in value relevance of accounting information in the IND-AS period. We have also found that the enhanced value relevance is uniformly distributed across firms irrespective of firm-size. JEL Classification Codes: M41.